Disseminated tuberculosis presenting as hypovolemic shock, hypernatremia with central diabetes insipidus - Ramaning Loni (Journal of Pediatric Critical Care, 2020)
Disseminated tuberculosis (TB) not uncommon in children in developing countries like India, and the spectrum of the disease varies in the different age groups. Tubercular meningitis can present as central diabetes insipidus, which is rare in children characterized by polydipsia and polyuria, because of the inability to concentrate urine secondary to defective synthesis of antidiuretic hormone. Here, we present 7-year-old girl child who was admitted with polyuria, polydipsia for the last 2–3 months with respiratory problems for 2–3 weeks with a family history of active pulmonary TB in a completely unimmunized child. She had disseminated TB involving the respiratory system and central nervous system, So, presented with hypovolemic shock with severe hypernatremia with dilute urine with encephalopathy. She was resuscitated and managed for a hypovolemic shock with metabolic derangement such as hypernatremia, requiring deficit fluid correction, vasopressin therapy, and antitubercular therapy to respond clinically. The child recovered completely without a neurological deficit.